The Influence of Corporate Culture and Employee Readiness in Realizing the Vision of PT. Citilink with Employee Wellbeing as a Moderating Variable - Yusuf, Adnan Husna; Setiadi, Iwan Kresna; Levianto, Jubei (Yayasan Sinergi Kawula Muda, 2026)
This study examined the relationship between corporate culture and employee readiness within the strategic framework of PT Citilink Indonesia’s vision to become a world-class low-cost carrier, with employee wellbeing included as a moderating variable. A quantitative research design was used, employing Partial Least Squares Structural Equation Modeling (PLS-SEM) on survey data collected from 250 employees across multiple directorates. The analysis showed that corporate culture had a significant positive effect on employee readiness, with the structural model demonstrating substantial explanatory power. Employee readiness was identified as an essential driver of organizational adaptability, enabling the company to align more effectively with strategic transformation goals. Employee wellbeing strengthened the effect of corporate culture on readiness, indicating that employees with higher emotional, social, psychological, and financial wellbeing were more likely to internalize organizational norms and respond proactively to change. These findings contribute to the literature by providing empirical evidence of the moderating role of wellbeing in cultural–behavioral dynamics within Indonesia’s aviation industry. Practically, the study underscores the importance of integrating corporate culture initiatives with sustainable wellbeing programs to enhance resilience, engagement, and competitiveness in increasingly dynamic airline environments.